Effect of Ultrasonic Shot Peening on the Cavitation Erosion Resistance of SLM316L Stainless Steel - WANG Zenan, CHENG Feng, WANG Shuo, SUN Jie (Cailiao Baohu, 2025)
In order to investigate the effect of ultrasonic shot peening on the cavitation erosion resistance of SLM316L stainless steel, the surface of SLM316L stainless steel was treated for varying durations (5, 25 and 45 min) using an ultrasonic shot peening apparatus.Subsequently, cavitation tests were conducted on both the untreated and shot-peened samples by means of an ultrasonic vibration device.The phase composition, residual stress, microhardness, surface morphology evolution and micro morphology of the samples were analyzed using X-ray diffraction (XRD), indentation tester, digital microhardness meter, digital 3D video microscope and scanning electron microscopy (SEM).Results showed that the SLM316L stainless steel sample and the ultrasonic shot peening sample exhibited different cavitation behaviors.Residual stresses were introduced into the surface of the samples by ultrasonic shot peening, the surface microstructure was refined, and the surface hardness was enhanced,which led to the mitigation of grain deformation caused by cavitation impacts.As a result,crack initiation was resisted,and cavitation damage was delayed.Additionally, the samples that were subjected to 25 and 45 min of shot peening underwent a transformation from austenite to martensite, and the martensite phase was found to further enhance the cavitation erosion resistance of the shot-peened specimens due to its superior hardening characteristics.The analysis of the weight loss curves and surface morphology during the cavitation process revealed that the 45 min shot-peened sample was found to exhibit the best cavitation erosion resistance.The cavitation erosion resistance of SLM316L stainless steel was effectively improved by the ultrasonic shot peening process, and it was demonstrated that extending the peening duration could further optimize the cavitation erosion resistance of the shot-peened samples.